untuk menganalisis teknik dasar ANALISIS TEKNIK DASAR OLAHRAGA FUTSAL PADA SISWA EKSTRAKULIKULER SMA NEGERI 1 TERAS: TEKNIK DASAR OLAHRAGA FUTSAL PADA SISWA EKSTRAKULIKULER SMA NEGERI 1 TERAS - Rusydy, Faisal Hanif Faras; Fatoni, Muhad; Sistiasih, Vera Septi (Universitas Hamzanwadi, 2024)
The purpose of this study was to analyse the basic techniques of futsal sport in extracurricular students of SMAN 1 Teras. This research used a quantitative approach. The subjects in this study were 10 futsal extracurricular students. The data collection techniques used were observation, interviews and documentation. The data analysis used is descriptive quantitative by classifying the type of data obtained from the observation sheet. The results of the data description that has been described by the researcher, that based on the results of the passing test can be seen from 15 people, namely 8 students in the very good category, 4 students in the good category, 4 students in the sufficient category and 1 student in the deficient category. Based on the results of the dribbling test can be seen from 15 students, namely 2 students in the excellent category, 4 students in the good category, 6 students in the sufficient category and 3 students in the deficient category. Based on the results of the shooting test can be seen from 15 students, namely 2 students in the excellent category, 4 students in the good category, 4 students in the sufficient category and 5 students in the deficient category. Based on the results of the heading test, it can be seen from 15 students, namely 42 students in the excellent category, 6 students in the good category, 4 students in the sufficient category and 1 student in the deficient category. So it can be concluded that the basic techniques of futsal sports for extracurricular students of SMAN 1 Teras are classified as very good.